THE BED-DEBTS ESTIMATE: A DEDUCTION FROM GROSS SALES. - Husband, George R. (The Accounting Review, 1942)
Abstract Because of its relation to both law and economics accounting contains a number of challenging problems. In the solution of these the accountant is influenced largely by the requirements of the basic philosophy and the purposes underlying and supporting his own field of endeavor. In some instances the legal point of view may dictate the decision, as for example in the division of corporate invested capital into capital stock and capital surplus; in other instances the economic or business point of view may be the influential factor, as when a building purchased on the contract plan is recorded as an asset even though title has not been acquired. In the main, however, accounting has its own story to tell. Where that can be done without too gross a violation of either of the supporting lines of endeavor the path of action appears to be clear. The accountant is at least free to go behind the formalistic and somewhat mechanical interpretation of the twin handmaiden to accounting that he represents.